Drive-by methodology to identify resonant bridges using track irregularity measured by high-speed trains. (September 2021) - Matsuoka, Kodai; Tanaka, Hirofumi; Kawasaki, Kyohei; Somaschini, Claudio; Collina, Andrea
Graphical abstract: Highlights: New drive-by detection method for resonant bridges in high-speed railway proposed. Difference in track irregularities for the first and last vehicles used. Applicability of the proposed method verified numerically. Proposed method applied to track irregularities in Japan's high-speed railways. Resonant bridges verified by in-situ bridge response measurements. Abstract: Resonance of railway bridges is a matter of major concern in high-speed railways because it reduces riding comfort, damages the attached structures, and decreases the strength of girder bodies. Although this abnormal behavior can be inspected using in situ displacement measurements taken from the ground, its investigation is tedious and, consequently, is very expensive. In this study, authors developed a novel drive-by system for high-speed railways to detect resonant bridges; the difference between two track irregularities at the same position using devices mounted on the first and last vehicles of a train was measured. This is based on the idea that the response of the last vehicle passing through the resonant bridge is attributed to the superposition of track irregularities and abnormal bridge displacement because of resonance mechanisms. However, the response of the first vehicle primarily arises from track irregularities since the resonance phenomenon is not yet sufficiently excited. The Resonance Detection Index (RDI), defined as the difference between the track irregularities measured by the devices mounted on the first and last vehicles, is used to emphasize the component excited by vehicle length to propose a methodology for detecting resonant bridges. Numerical simulations clarify that bridge span and track irregularity have greater effects on the RDI than either measurement noise or positioning error. Track irregularity may cause the RDI to vary by ± 2 mm depending on vehicle length wave component of the track irregularity. Consequently, this study demonstrates that resonant bridges with spans between 20 and 60 m can be detected using the proposed RDI. Finally, the proposed method was applied to track irregularity measurements using actual high-speed trains operating in Japan. More than ten bridges, out of more than 800 bridges, were detected as resonant bridges according to RDI. In situ displacement measurements were performed for three of these bridges, demonstrating the presence of resonance phenomenon and thereby validating the proposed method.